As competências dos profissionais da área de gestão de pessoas/recursos humanos - Lima, Claudia Maria Pereira de (2012)
This work investigates how the professionals of Personnel Management (PM) / Human Resources (RH) mobilize their competences in work situations. The discourse of competence gained prominence as a model of human resource management, indicating a strong change in the model of evaluative judgments about workmanship that goes to appreciate a new profile of worker capable of inventing the answers in a technical environment and social complex and unstable.. Although the model of human resource management was being centered in the discourse of competence and, despite the recognition of the need to change the practices of PM / HR to answer the new demands, it is observed that there are not sufficient studies that deal with the day to day work of professionals who working in this area. Thus, it is important to know the mobilized competencies by these professionals to answer the demands that go with them in their daily lives. For this, the general objective of this study is to understand how the professionals who working in this area mobilize their competencies in work situations. Such purpose unfolds in the following specific objectives: to identify the competencies that professionals in PM / HR mobilize in work situations; show how they do to deal with the variability that could arise; detect innovations that they produce when variabilities appear; identify competencies that they judge necessary, even if they do not yet have. The theoretical contribution of this study is based on contributions from the discussions on competence, especially from the work of Philippe Zarifian pierced by a glance through the reflections of Ergology brought by Yves Schwartz. As to the method, this research is characterized by a field study done by exploiting qualitative aspects of the speeches of the participants. The instrument used was the semi-structured interview guide. For data analysis, the content analysis was chose, with clipping themes. Participated in the survey, eleven professionals in Personnel Management / Human Resources who working in companies located in the metropolitan area of João Pessoa / PB. Of these participants, nine were female and two are male. The average age of male participants is 43 years while the average age of participants is 28 years. With regard to educational level, the nine women participants have training as a graduate in Psychology, while male participants have training in Administration. Regarding the mobilization of competences in work situations, it became clear the relationship between vocational training, professional development and the specific skills that manifest themselves in day to day work to drive competence - competence in action - from professionals GP / HR.